Oseltamivir treatment of influenza A and B infections in infants. Issue 5 (3rd May 2021) - Mattila, Janna‐Maija; Vuorinen, Tytti; Waris, Matti; Antikainen, Petri; Heikkinen, Terho
Abstract: Background: Oseltamivir treatment is currently the only way of managing influenza in young infants for whom influenza vaccines are not licensed, but little data exist on the effectiveness of the treatment in this age group. Methods: In a prospective study, we enrolled 431 newborn infants and followed them up for 10 months during their first respiratory season (September 2017‐June 2018). During each respiratory illness, we examined the infants and obtained nasopharyngeal specimens for determination of the viral etiology. Infants with influenza were re‐examined at short intervals, and additional nasopharyngeal specimens were obtained at each visit for measuring the viral load. All infants with symptoms <48 hours received oseltamivir treatment. The parents filled out daily symptom diaries. Results: Among 23 infants with influenza A, the mean total duration of illness in oseltamivir recipients was 82.1 hours, compared with 253.5 hours in infants without treatment ( P  = .0003). For infants with influenza B, the corresponding durations were 110.0 and 173.9 hours, respectively ( P  = .03). In infants with influenza A, total symptom scores were significantly lower in oseltamivir‐treated infants at all time points between days 3 and 11 after the onset of therapy. In most children with either influenza A or B, viral antigen concentrations declined rapidly within 1‐2 days after the initiation of oseltamivir treatment. Conclusions: Oseltamivir treatment of infants with influenza rapidly decreased the viral load in nasopharyngeal secretions and shortened the duration and severity of symptoms. The clinical effectiveness of oseltamivir appeared to be greater against influenza A than against influenza B infections.